(1212) On the use of fictitious bounds in tree search algorithms حول استخدام الحدود الوهمية في خوارزميات البحث الشجري - Bazraa, Mokhtar S.; Elshafei, Alwalid N. (The Institute Of National Planning., 2018)
Tree search algorithms for a minimization problem can be classified under two major categories. the first (breadth) category attempts to search the tree by branching from the node with the smallest lower bound. This serves to minimize the portion of the tree which is explicitly explored.